'My father is a gardener … ': A systematic narrative review on access and use of the garden by people living with dementia. (March 2021) - Newton, Rita; Keady, John; Tsekleves, Emmanuel; Adams OBE, Sue
Abstract: In this narrative review we explored existing evidence about people living with dementia accessing and using their garden in both the domestic home and care home settings. The review revealed that gardens enabled people living with dementia to maintain a sense of continuity and identity by connecting to nature, people, and to the moment, whilst managing everyday risks. However, the review also revealed a number of areas where attention and study is urgently required, including: increasing the visibility and presence of people living with dementia in the literature; developing more participatory, creative and co-research designs; and exploring the person living with dementia's denial of access to garden spaces. Highlights: Gardens enable a sense of continuity and identity for people living with dementia. 'Meaningful doing' enhances a sense of agency and well-being for people living with dementia. Connecting to nature, people, and to the moment are important for people living with dementia. Restricting access to the garden negatively impacts on people living with dementia. Relatively little is known about the domestic garden in comparison to care home gardens.